Reconstructing the graviton - Bonanno, Alfio; Denz, Tobias; Pawlowski, Jan M.; Reichert, Manuel (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 001 (2022) Reconstructing the graviton
Gesehen am 23.09.2022